2019
DOI: 10.3389/fpsyg.2019.02759
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Social Relational Emotions for Human-Nature Connectedness

Abstract: Little is known about the psychological processes through which people connect to nature. From social psychology, we know that emotions play an essential role when connecting to others. In this article, we argue that social connectedness and connectedness to nature are underpinned by the same emotions. More specifically, we propose that social relational emotions are crucial to understanding the process through which humans connect to nature. Beside other emotions, kama muta (Sanskrit: being moved by love) mig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 67 publications
1
36
0
4
Order By: Relevance
“…While the above factors are discussed as independent contributors to wellbeing, they are all interrelated components of a wider framework (GENIAL) and have been found to promote each other to some degree (Chen & Kee, 2008;Dadvand et al, 2016;Elavsky et al, 2005;Holt-Lunstad et al, 2010;Kok et al, 2013;Petersen et al, 2019). The nation-wide, lockdown associated with the COVID-19 pandemic in the UK provided a unique opportunity to explore the impact on and contributors to wellbeing during a time of great suffering, the focus of Second Wave Positive Psychology (PP 2.0), also described as existential positive psychology (Wong, in press.;.…”
Section: Introductionmentioning
confidence: 99%
“…While the above factors are discussed as independent contributors to wellbeing, they are all interrelated components of a wider framework (GENIAL) and have been found to promote each other to some degree (Chen & Kee, 2008;Dadvand et al, 2016;Elavsky et al, 2005;Holt-Lunstad et al, 2010;Kok et al, 2013;Petersen et al, 2019). The nation-wide, lockdown associated with the COVID-19 pandemic in the UK provided a unique opportunity to explore the impact on and contributors to wellbeing during a time of great suffering, the focus of Second Wave Positive Psychology (PP 2.0), also described as existential positive psychology (Wong, in press.;.…”
Section: Introductionmentioning
confidence: 99%
“…Self-connection is also associated with self-actualisation (Klussman et al, 2020a,b,c) and connectedness with others (Kok and Fredrickson, 2010;Kok et al, 2013), which has been described as a psychological need (Baumeister and Leary, 1995;Deci and Ryan, 2000). Social connectedness is associated with the social relational emotions including gratitude, compassion and awe, all of which are powerful determinants of prosocial behaviour (Stellar et al, 2017;Petersen et al, 2019). These emotions have been associated with higher levels of vagal function (Childre, 2004;Shiota et al, 2011;Bello et al, 2020), and recent thinking suggests that they may be involved in feelings of connection to the natural environment (Petersen et al, 2019) which are again associated with vagal nerve functioning (Richardson et al, 2016).…”
Section: Rethinking Wellbeingmentioning
confidence: 99%
“…The evolutionary model for the wellbeing benefits of nature (Richardson et al, 2016) features the vagus nerve within a physiologically based model of affect. Interestingly, meta-analysis (Bello et al, 2020) has demonstrated a role for the vagus nerve in feelings of compassion, an experience supporting connection to self, others and nature (Neff, 2003;Petersen et al, 2019). Compassion is often facilitated through loving kindness meditation, which builds positive emotions, promotes feelings of social connectedness and raises levels of vagal function in an upward spiral relationship (Kok et al, 2013).…”
Section: The Vagus Nerve and Wellbeingmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Tam and Milfont [20] persuasively argue that cultural conceptions of nature enable, limit, and shape nature experiences. This argument has also explicitly been stressed for social relational emotions elicited by interactions with nature [21,22]. Grasping such cultural situatedness is of particular importance for solo settings, since the practice of being solitary as an end in itself is historically and culturally rooted.…”
Section: Solo and (Subjective) Well-beingmentioning
confidence: 99%